Effectiveness of Television Cigarette Advertising Regulation Based on Minister of Health Regulation No. 56/2017 Concerning the Inclusion of Health Warnings and Health Information on Tobacco Product Packaging - Putu Yudi Pradnyana; I Wayan Gede Artawan Ekaputra (Journal of Law, Politic and Humanities, 2025)
The regulation of cigarette advertising on television is a crucial issue in protecting public health, particularly in efforts to reduce the prevalence of smoking in Indonesia. This study aims to assess the effectiveness of the Minister of Health Regulation No. 56/2017, which mandates health warnings and health information on tobacco product packaging, in mitigating the negative impacts of cigarette advertisements especially among vulnerable groups such as children and adolescents. Employing a normative method with a legislative approach alongside descriptive analysis, the research reveals that while the regulation has successfully imposed restrictions on both the airtime and content of cigarette advertisements, its implementation is hindered by several challenges. These obstacles include insufficient oversight, the absence of stringent sanctions, and resistance from the tobacco industry. Furthermore, the study finds that despite offering initial protection, exposure to cigarette advertising on television continues to contribute to the normalization of smoking behavior within the community. Comparative analysis with regulations in other nations, notably Australia, indicates that a complete ban on cigarette advertising is more effective in lowering smoking prevalence. In light of these findings, the study recommends enhancing monitoring mechanisms, enforcing stricter sanctions, and considering a total ban on television cigarette advertisements to further reinforce public health protection.